"Progess, coexistence and intellectual freedom" - "Sakharov, Andrei D." (Middlesex, 1982)
Sakharov was instrumental in the success of the soviet nuclear program in the later part of World War 2 and beyond. In this book Sakharov explores what the nuclear age means to man and how we can prevent our own destruction. He goes beyond exploring measures for the prevention of nuclear war and explores all areas of global life. Human civilization is threatened by, on top of nuclear war, famine, "stupefaction from the narcotic of mass culture", bureaucratized dogmatism, the spread of mass myths that support cruel demagogues, and the consequences of (what is now referred to as) climate change.
Keywords: International cooperation